2010
DOI: 10.2202/1935-1682.2349
|View full text |Cite
|
Sign up to set email alerts
|

IQ and Family Background: Are Associations Strong or Weak?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 17 publications
5
46
0
Order By: Relevance
“…Our estimates are based on data from SOEP, which is a large representative household survey that provides measures of cognitive skills from two ultra-short IQ tests, as well as self-rated measures of locus of control, reciprocity, and the Big Five personality traits. Previous analyses for Sweden and the US are restricted because they are based only on males (Björklund et al, 2010;Björklund and Jäntti, 2012) and/or use few non-cognitive skill measures (i.e., locus of control (Mazumder, 2008) and leadership skills (Björklund and Jäntti, 2012)) and are based on only a single measurement at one point in time. Hence, our study contributes to the literature by providing evidence on sibling correlations using broader measures and repeated measurements of skills and by including both men and women.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our estimates are based on data from SOEP, which is a large representative household survey that provides measures of cognitive skills from two ultra-short IQ tests, as well as self-rated measures of locus of control, reciprocity, and the Big Five personality traits. Previous analyses for Sweden and the US are restricted because they are based only on males (Björklund et al, 2010;Björklund and Jäntti, 2012) and/or use few non-cognitive skill measures (i.e., locus of control (Mazumder, 2008) and leadership skills (Björklund and Jäntti, 2012)) and are based on only a single measurement at one point in time. Hence, our study contributes to the literature by providing evidence on sibling correlations using broader measures and repeated measurements of skills and by including both men and women.…”
Section: Resultsmentioning
confidence: 99%
“…Intergenerational transmission of cognitive skills has been analyzed in the contexts of Scandinavia (Black et al, 2009;Björklund et al, 2010;Grönqvist et al, 2010), the US (Agee and Crocker, 2002), the UK (Brown et al, 2011), and Germany Anger, 2012). By contrast, the economic literature contains far less evidence on the intergenerational transmission of non-cognitive skills.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An important feature of the reform is that the timing of the roll-out varied across municipalities, which gives us variation in reform exposure both within and between 1 The range of topics that has been explored includes, but is not limited to, the effect of parental education on children's educational outcomes (Black et al 2005;Magnuson 2007; Page 2009) cognitive and non-cognitive abilities (Lundborg et al 2014) and health (Currie and Moretti 2003;McCrary and Royer 2006;Lundborg et al 2014), the effect of parental health on children's outcomes Persson and Rossin-Slater 2014), and transmission of IQ and cognitive and non-cognitive skills (Black et al 2009;Anger and Heineck 2009;Gronqvist et al 2009;Björklund et al 2010). In most cases, studies that have looked into the causal effects of parental education have found positive and significant effects of increases in both or one of the parents' educational attainments on children's outcomes.…”
Section: Introductionmentioning
confidence: 99%